Sweet Pepper (Capsicum annuum L.) Fruits Contain an Atypical Peroxisomal Catalase That Is Modulated by Reactive Oxygen and Nitrogen Species - Marta Rodríguez-Ruiz; Salvador González-Gordo; Amanda Cañas; María Jesús Campos; Alberto Paradela; Francisco J. Corpas; José M. Palma (MDPI AG, 2019)
During the ripening of sweet pepper (Capsicum annuum L.) fruits, in a genetically controlled scenario, enormous metabolic changes occur that affect the physiology of most cell compartments. Peroxisomal catalase gene expression decreases after pepper fruit ripening, while the enzyme is also susceptible to undergo post-translational modifications (nitration, S-nitrosation, and oxidation) promoted by reactive oxygen and nitrogen species (ROS/RNS). Unlike most plant catalases, the pepper fruit enzyme acts as a homodimer, with an atypical native molecular mass of 125 to 135 kDa and an isoelectric point of 7.4, which is higher than that of most plant catalases. These data suggest that ROS/RNS could be essential to modulate the role of catalase in maintaining basic cellular peroxisomal functions during pepper fruit ripening when nitro-oxidative stress occurs. Using catalase from bovine liver as a model and biotin-switch labeling, in-gel trypsin digestion, and nanoliquid chromatography coupled with mass spectrometry, it was found that Cys377 from the bovine enzyme could potentially undergo S-nitrosation. To our knowledge, this is the first report of a cysteine residue from catalase that can be post-translationally modified by S-nitrosation, which makes it especially important to find the target points where the enzyme can be modulated under either physiological or adverse conditions.